2019
DOI: 10.1177/0300060519876796
|View full text |Cite
|
Sign up to set email alerts
|

GSTA3 regulates TGF-β1-induced renal interstitial fibrosis in NRK-52E cells as a component of the PI3K–Keap1/Nrf2 pathway

Abstract: ObjectiveTo evaluate the effect of GSTA3 within the PI3K–Keap1/Nrf2 pathway in renal interstitial fibrosis (RIF).MethodsAn in vitro RIF model with TGF-β1 stimulation in NRK-52E cells was established to identify potential signaling pathways that modulate GSTA3. Changes in GSTA3 expression were observed in the RIF model after silencing or enhancing Nrf2 expression. Changes in GSTA3, Keap1, and Nrf2 expression were detected after blocking the upstream of the Keap1/Nrf2 signaling pathway (including MAPK and PI3K/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Transmembrane 26 (Tmem26) is a surface marker protein of beige adipocytes, and M2 macrophage activation contributes to beige fat development [ 27 , 28 ]. Glutathione S-transferase alpha 3 (Gsta3) is a member of the GST family and is a detoxification enzyme that protects against oxidative stress [ 29 ]. Increased oxidative stress promotes osteoclastic bone remodeling and decreased bone loss [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transmembrane 26 (Tmem26) is a surface marker protein of beige adipocytes, and M2 macrophage activation contributes to beige fat development [ 27 , 28 ]. Glutathione S-transferase alpha 3 (Gsta3) is a member of the GST family and is a detoxification enzyme that protects against oxidative stress [ 29 ]. Increased oxidative stress promotes osteoclastic bone remodeling and decreased bone loss [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…GSTA3, which is one of the most important members of the glutathione transferase family and is involved in the detoxification and cellular defense ( Hayes et al, 2005 ), it was reported to attenuate renal interstitial fibrosis in vivo and in vitro by inhibiting the activity of the TGF-β1 signaling pathway ( Xiao et al, 2016 ; Xiao et al, 2019 ) and inhibited liver fibrosis through the suppression of the MAPK and GSK-3β signaling pathways ( Chen et al, 2019 ), suggesting that GSTA3 is an effective anti-fibrosis target. S100A9 was not only identified as a marker for idiopathic pulmonary fibrosis ( Hara et al, 2012 ; Yamashita et al, 2021 ), but also aggravated dermal fibrosis induced by bleomycin in mice via activation of ERK1/2 MAPK and NF-κB pathways ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, Keap1 negatively regulates Nrf2, inhibiting its activity and thereby maintaining cell homeostasis. When exposed to poisons or certain stimuli, the Keap1-Nrf2 dimer is automatically separated, and Nrf2 is activated and transferred to the nucleus to bind to ARE, thereby activating the expression of antioxidant enzymes and phase II detoxification enzyme genes [ 44 , 45 ]. Therefore, the decrease of antioxidant enzyme activity and the increase of GPX1 expression in intestinal oxidative stress induced by ZEA may be the result of an oxidative stress signal induced by the Keap1-Nrf2 signaling pathway and the regulation of antioxidant enzyme expression by the transcription factor Nrf2.…”
Section: Discussionmentioning
confidence: 99%